Structure of staphylococcal alpha-hemolysin, a heptameric transmembrane pore. - Song, L; Hobaugh, MR; Shustak, C; Cheley, S; Bayley, J; Gouaux, J (1996)
The structure of the Staphylococcus aureus alpha-hemolysin pore has been determined to 1.9 A resolution. Contained within the mushroom-shaped homo-oligomeric heptamer is a solvent-filled channel, 100 A in length, that runs along the sevenfold axis and ranges from 14 A to 46 A in diameter. The lytic, transmembrane domain comprises the lower half of a 14-strand antiparallel beta barrel, to which each protomer contributes two beta strands, each 65 A long. The interior of the beta barrel is primarily hydrophilic, and the exterior has a hydrophobic belt 28 A wide. The structure proves the heptameric subunit stoichiometry of the alpha-hemolysin oligomer, shows that a glycine-rich and solvent-exposed region of a water-soluble protein can self-assemble to form a transmembrane pore of defined structure, and provides insight into the principles of membrane interaction and transport activity of beta barrel pore-forming toxins.